Water quality used in milking parlors of dairy farms in midwest of Santa Catarina State, Brazil - João, Jucimara Horstmann; Rosa, Carlos André da Veiga Lima; Thaler Neto, André; Picinin, Lídia Cristina Almeida; Fuck, Jeferson José; Marin, Guilherme (Revista de Ciências Agroveterinárias, 2011)
The aim of this study was to evaluate the quality of water used on dairy farms in the Midwest region of Santa Catarina State, Brazil, considering the current legal Standards of drinking water. A structured questionnaire was applied to farmers and water samples were collected in 76 dairy farms for chemical and microbiological analysis of the water. Hardness, pH, Standard Plate Count of heterotrophic bacteria counting (PPC), total and fecal coliforms were analyzed. The results of the application questionnaires were analyzed through the test χ2. To evaluate the influence of the data obtained from the application of questionnaires on the water quality, data were submitted to analysis of variance. The water was collected from protected sources, source Caxambu, artesian well or unprotected sources. Mean PPC was 3,2±0,83log10 UFC mL-1, with only 5% of the samples without total coliforms and 24% contaminated by fecal coliforms. The presence or absence of fecal coliforms was not related to the PPC. The PPC was not related to the type of water source, but farms with water tank had water with better microbiological quality. The pH and hardness of the water were within legal limits and not affect the PPC of the water. The water used in dairy farms of the Midwest region of Santa Catarina State, Brazil, has coliform contamination, characterizing the need of actions that improve its quality or additional treatments in order to adapt it to legal standards.